2017
DOI: 10.1590/2359-3997000000288
|View full text |Cite
|
Sign up to set email alerts
|

Serum nesfatin-1 levels are decreased in pregnant women newly diagnosed with gestational diabetes

Abstract: Objective: To investigate serum nesfatin-1 levels at 24-28 weeks of pregnancy in women newly diagnosed with gestational diabetes and determine the association of nesfatin-1 with several metabolic parameters. Subjects and methods: Forty women newly diagnosed with gestational diabetes at 24-28 weeks of pregnancy and 30 healthy pregnant women matched in age and gestational week were included in this cross-sectional study. Serum nesfatin-1 levels were analyzed using ELISA, and the relationship between nesfatin-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…There are only a few studies that have analyzed the serum level of nestafin-1 in pregnant woman with GDM, and the data are not clear [24,25,26,27]. In our study, we observed that in patients with GDM, nesfatin-1 serum concentrations remained significantly lower than in the group of healthy pregnant women (5.15 ± 3.51 vs. 6.69 ± 4.21 ng/mL).…”
Section: Discussioncontrasting
confidence: 62%
“…There are only a few studies that have analyzed the serum level of nestafin-1 in pregnant woman with GDM, and the data are not clear [24,25,26,27]. In our study, we observed that in patients with GDM, nesfatin-1 serum concentrations remained significantly lower than in the group of healthy pregnant women (5.15 ± 3.51 vs. 6.69 ± 4.21 ng/mL).…”
Section: Discussioncontrasting
confidence: 62%
“…In the previous researches, the correlation between nesfatin-1 levels and BMI remained unclear [12,37]. The findings from the meta-analysis, manifested that women with GDM and a high BMI displayed substantially lower nesfatin-1 concentrations than women with a normal weight suffering from GDM, which was in line with the negative relationship between nesfatin-1 concentration and BMI.…”
Section: Discussionmentioning
confidence: 55%
“…Among the 806 articles retrieved, 31 were eligible; 14 were FABP4 studies [ 8 , 17 19 , 26 – 36 ], seven were nesfatin-1 studies [ 10 , 12 , 20 , 37 – 40 ], seven were OC studies [ 14 , 21 , 41 – 45 ], and three articles covered both FABP4 and nesfatin-1 [ 11 , 46 , 47 ]. The 31 studies involved 4590 participants; 2059 were GDM patients and 2531 were healthy pregnant women [ 8 , 10 12 , 14 , 17 21 , 26 – 47 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with gestational diabetes mellitus serum NUCB2/nesfatin-1 concentrations, NUCB2/nesfatin-1 levels in cord blood and protein expression of NUCB2/nesfatin-1 in subcutaneous fat were higher than in healthy pregnant subjects [ 106 ]. Inconsistently, a previous [ 107 ] and a subsequent [ 108 ] study showed the opposite regulation, with decreased serum NUCB2/nesfatin-1 levels and a positive association between NUCB2/nesfatin-1 and gestational week [ 108 ]. These discrepant results might be due to, although subtle, differences in age (29.6 ± 5.3 vs .…”
Section: Implications Of Nesfatin-1 In Blood Glucose Homeostasismentioning
confidence: 96%